2019
DOI: 10.1111/ajag.12667
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of an organisational culture change intervention in residential aged care facilities

Abstract: Objective To develop and evaluate an organisational culture change intervention for residential aged care settings. Methods This study was undertaken in five residential aged care facilities (RACFs). All staff working within participating RACFs were invited to take part. Participatory action research was used to develop a structured approach, supporting small workgroups of staff in each facility to undertake change cycles, focusing on improved leadership, teamwork and communication. Qualitative data were gathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…[30] Similarly, Venturato, Horner, and Etherton-Beer (2019) identify that nurses can improve their practice through critical reflection on their practice, and critical reflection was an ongoing activity of the CLD workshop, focused on improving the LPNs' practice in SL. [31] The study findings suggested that a regularly scheduled CLD workshop offered in the workplace could improve participants' team communication, empowerment, relationships, and teamwork.…”
Section: Challengesmentioning
confidence: 86%
“…[30] Similarly, Venturato, Horner, and Etherton-Beer (2019) identify that nurses can improve their practice through critical reflection on their practice, and critical reflection was an ongoing activity of the CLD workshop, focused on improving the LPNs' practice in SL. [31] The study findings suggested that a regularly scheduled CLD workshop offered in the workplace could improve participants' team communication, empowerment, relationships, and teamwork.…”
Section: Challengesmentioning
confidence: 86%
“…The strength of this work is its grounding in an iterative development process informed by empiric data comprising of previous studies of educational interventions and organisational culture in RACF, as well as piloting of the intervention and engaging consumers in the process 6,8,10,12 . Notwithstanding these strengths, interpretation of the results is limited by a potential for volunteer bias, and generalisability is limited by the small number of participating RACF.…”
Section: Discussionmentioning
confidence: 99%
“…To support sustainable culture change in residential aged care, we developed and piloted the Towards Organisational Culture Change (TOrCCh) intervention 6,12 . Participatory action research was used to develop and pilot a structured approach supporting small work groups of staff in each of the eight facilities to undertake quality improvement cycles focusing on improving leadership, teamwork and communication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further key facet of this orientation is represented by the occupational, organizational, and environmental health of staff working in RFs. In fact, it is necessary that operators are capable of caring work in their area of expertise, but also of cooperating within a multidisciplinary team that is open to discussion and improvement [ 17 , 18 ]. In addition, they should be able both to relate to the patient and his or her caregivers (often family members) with empathy, listening skills, emotional closeness, and affective exchange [ 19 , 20 ], and to know how to cope with critical relational situations, which can be marked by fear, suffering, anger, conflict, and misunderstanding [ 21 ], and not infrequently by despair and grief [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%